Using participatory research to communicate environmental health risks to First Nations communities in Canada. Issue 1 (2nd January 2016) - Sharp, Donald; Black, Andrew; Mitchell, Judy
ABSTRACT: This paper describes a network of three interconnected, multidisciplinary research projects designed to investigate environmental health issues faced by First Nations in Canada. These projects, developed in collaboration with academia, used a participatory approach meant to build capacity, raise awareness, and initiate change. The first project, which began in British Columbia in 2008, gathered information on the traditional diet; for example, its composition, nutritional quality, and potential for chemical exposure. This 10-year, Canada-wide project served as a model for two follow-up projects: one on biomonitoring and another on indoor air quality. All three projects provided community ownership over the data and communicated results in a culturally sensitive manner to encourage interest in research and initiate risk reduction activities. The Assembly of First Nations, a national advocacy organization representing over 630 First Nations communities across Canada, participated in all aspects of the research while coordinating communications and arranging timely dissemination of results. These projects showed how properly executed, community-based research can be a valuable tool for stimulating interest in scientific studies while promoting self-reliance, components often missing from academic research.